Psychometric properties of the Lithuanian version of The NEO PI-R - Žukauskienė, Rita; Barkauskienė, Rasa (Psichologija, 2006)
Personologists from many countries have consulted the natural language when developing personality taxonomies. Presently, the Big Five factor structure represents the most popular lexically derived personality taxonomy. The Five-Factor model consists of hierarchical trait organization and comprises five basic personality dimensions or factors. These factors are often termed the “Big Five” and represent the general consensus in differential psychology. The five factors are named Neuroticism (N), Extraversion (E), Openness (O), Agreeableness (A), and Conscientiousness (C). The five-factor model developed by Costa and McCrae (1985) is operationalized in the NEO Personality Inventory (NEO-PI R) (Costa, McCrae, 1992).The replicability and ubiquity of the Big Five have led many personality psychologists to advocate this structure as a basic framework for personality description and assessment. The generalizability across different cultures and languages is crucial for the evaluation of a personality taxonomy or structure. When using selfreports, it is critical for trait psychologists to ascertain whether the same sets of assertions are equivalent, i. e. whether they convey the same meanings across languages and cultures that are different from the one in which they were originally generated. Like any kind of assessment based on informants, NEO PI-R is susceptible to the influence of culture and language. This makes analysis of psychometric properties and standardization necessary for the culture in which they are going to be used.This study examined the psychometric properties of the Lithuanian version of the NEO PI-R in a sample of 317 adults (104 men and 213 women, age 19–64). With respect to reliability, although internal consistency and homogeneity estimates of five dimensions were all acceptable the results suggested rather high levels of internal consistency and homogeneity for most of the facet scales with few exceptions. The similarity of reliability with English studies gives to these dimensions and facets scales, the needed stability for future practical applications, as well as for research.Next, in this study we deal with the examination of construct or structural equivalence. To determine the structure of its underlying factor, the Lithuanian NEO PI-R scores of item-level (240 items) were subjected to the principal components analysis with varimax rotation. Factorial analysis identified the same five factors as in other countries. 28 from 30 facet scales (all, except Impulsivity (N5) and Activity (E4)) had chief loadings in the predicted factor. This confirms the generalizability and sufficient fit to the theoretical model.Third, our results with respect to mean scores revealed significant differences between the Lithuanian sample and the USA normative sample for Neuroticism, Openness to Experience and Conscientiousness domains. Overall, this study has provided evidence to support the conjecture that personality structure transcends cultural differences. The conclusions of this study are in line with these recent findings, and they support McCrae and Costa’s (1997) hypothesis that the FFM represents a universal personality structure.
Keywords: personality traits; Five Factor moder; NEO PI-R